0406 The Effects Of Cbt-i On Cognitive Functioning In Individuals With Insomnia And Mild Cognitive Impairment. (27th April 2018) - Goldstein-Piekarski, A N; O'Hora, K; Buchanan, A; Lee, C; Hernandez, B; Zeitzer, J M; Friedman, L; Kushida, C; Yesavage, J
Abstract: Introduction: Insomnia and Mild Cognitive Impairment (MCI) are prevalent and often comorbid disorders in older adult populations. Insufficient sleep may exacerbate impaired cognitive functioning, potentially representing a causal factor and treatment target for MCI in some individuals. Supporting this, a recent study demonstrated that Cognitive Behavioral Therapy for Insomnia (CBT-I) not only improves sleep, but also cognitive functioning in older individuals in residential settings with comorbid insomnia and MCI. We sought to extend these findings utilizing an ongoing study of the behavioral and cognitive components of CBT-I in a sample of community-living older adults. Methods: Fifty-seven independent-living, older adults (mean age=68.2, 33% male) with insomnia received either the behavioral, cognitive, or both components of CBT-I treatment. All participants were grouped as a single treatment group for this analysis. Participants completed the Montreal Cognitive Assessment (MoCA) at baseline. In addition, the Insomnia Severity Index, D-KEF Color-Word Interference Test (inhibition and task-switching), and Repeatable Battery for Assessment of Neuropsychological Status (RBANS; verbal memory recall and recognition) were administered at baseline and six months after treatment. MoCA scores indicated 16 participants with MCI (MoCA < 26) and 41 non-MCI participants. Results: Two-way repeated measures ANOVAs with one within (time: pre- versus post-treatment) and one between (MCI status: MCI versus non-MCI) subjects factors revealed significant main effects of time in reducing insomnia severity ( p<0.0001 ) as well as improving inhibition (p=0.004) and verbal memory (p=0.007) performance (recall) in both MCI and non-MCI individuals. There were no significant time x MCI status interaction effects for these measures (p's>0.05). No interaction, nor main effects of time were found for measures of task-switching nor verbal memory recognition (p's>0.05). Conclusion: These findings replicate and extend work demonstrating that non-pharmacological insomnia treatments can improve insomnia symptoms and may improve cognitive abilities in individuals with and without MCI. They also add additional support to the hypothesis that sleep is an intervention target for improving cognitive abilities in those with insomnia. Support (If Any): NIMH 1R01MH101468-01 and the MIRECC at the VA Palo Alto Health Care System.